Dairy safety survey: 2012 - Janke, James; Trechter, David (My University, 2012)
This survey was designed to gather information about the safety practices of members of the Professional Dairy Producers of Wisconsin (PDPW) and their interest in professional development opportunities with respect to safety on dairy farms.
30 p.
Keywords: Agriculture--Wisconsin; Safety practices; Professional Dairy Producers of Wisconsin